2011
DOI: 10.1049/iet-cta.2010.0360
|View full text |Cite
|
Sign up to set email alerts
|

Global practical stabilisation of large-scale hydraulic networks

Abstract: Proportional feedback control of a large scale hydraulic network which is subject to structural changes is considered. Results regarding global practical stabilization of the non-linear hydraulic network using a set of decentralized proportional control actions are presented. The results show that closed loop stability of the system is maintained when structural changes are introduced to the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The results presented here represents an important extension of the analytical results presented in [2][3][4][5]. In [3], it was shown that semi-global practical output regulation is achievable using the proposed control architecture with constrained proportional control actions.…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…The results presented here represents an important extension of the analytical results presented in [2][3][4][5]. In [3], it was shown that semi-global practical output regulation is achievable using the proposed control architecture with constrained proportional control actions.…”
Section: Introductionsupporting
confidence: 57%
“…In the work presented here, a set of decentralised proportional control actions will be in the focus. The control strategy has previously been introduced in [2][3][4][5]. The individual control signal relies only on information obtained at the individual end-user.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4. Contrary to the result with the continuous proportional control actions (Jensen and Wisniewski, 2010), it is evident from Fig. 4 that a single unique equilibrium point can generally not be achieved when the quantized version of the proportional control actions are used.…”
Section: Numerical Resultsmentioning
confidence: 64%